Optimalisasi Pesan Moderasi Beragama di Era Digital: Studi Website NU Online - Muhammad Fanshoby; Khofifah Nur Hidayat (El Madani : Jurnal Dakwah dan Komunikasi Islam, 2024)
This research focuses on optimizing religious moderation messages through Search Engine Optimization (SEO) on NU Online, an Islamic website platform in Indonesia. Using a constructivist paradigm with a descriptive qualitative approach, this study explores how religious moderation messages are constructed and disseminated through Computer-Mediated Communication (CMC) and SEO. Data was collected through interviews, observations, and documentation, with a specific analysis on the popular article titled "Moderation of Religion and Its Urgency" on NU Online. The results show that NU Online has effectively implemented keyword research and On-Page SEO but is lacking in Off-Page SEO implementation. This indicates that the religious moderation messages are not yet fully optimized on this website. These findings underscore the importance of comprehensive SEO strategies to enhance the visibility and dissemination of religious moderation messages. The study recommends increasing the use of Off-Page SEO on Islamic websites. This includes the development of models or practical guides to optimize online religious content, encompassing aspects of keyword research, inclusive content, and effective campaign strategies. These implications are crucial for expanding the reach and impact of religious moderation messages, especially in the current digital era. The study also opens opportunities for further research on the influence of SEO on the dissemination of religious messages on the internet. The implementation of effective SEO strategies is expected to enhance the effectiveness of disseminating religious moderation messages through NU Online and other Islamic websites in Indonesia.